Hardware Protection through Obfuscation - Forte, Domenic; Bhunia, Swarup; Tehranipoor, Mark M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book introduces readers to various threats faced during design and fabrication by today's integrated circuits (ICs) and systems. The authors discuss key issues, including illegal manufacturing of ICs or "IC Overproduction," insertion of malicious circuits, referred as "Hardware Trojans", which cause in-field chip/system malfunction, and reverse engineering and piracy of hardware intellectual property (IP). The authors provide a timely discussion of these threats, along with techniques for IC protection based on hardware obfuscation, which makes reverse-engineering an IC design infeasible for adversaries and untrusted parties with any reasonable amount of resources. This exhaustive study includes a review of the hardware obfuscation methods developed at each level of abstraction (RTL, gate, and layout) for conventional IC manufacturing, new forms of obfuscation for emerging integration strategies (split manufacturing, 2.5D ICs, and 3D ICs), and on-chip infrastructure needed forsecure exchange of obfuscation keys- arguably the most critical element of hardware obfuscation.
Part 1: Hardware Obfuscation Preliminaries -- Introduction to Hardware Obfuscation: Motivation, Methods and Evaluation -- VLSI Test and Hardware Security Background for Hardware Obfuscation -- Part 2: Logic-based Hardware Obfuscation -- Logic Encryption -- Gate Camouflaging-based Obfuscation -- Permutation-Based Obfuscation -- Protection of Assets from Scan Chain Vulnerabilities through Obfuscation -- Part 3: Finite State Machine (FSM) Based Hardware Obfuscation -- Active Hardware Metering by Finite State Machine Obfuscation -- State Space Obfuscation and its Application in Hardware Intellectual Property Protection -- Structural Transformation-based Obfuscation -- Part 4: Hardware Obfuscation Based on Emerging Integration Approaches -- Part IV Hardware Obfuscation Based on Emerging Integration Approaches -- Split Manufacturing -- Obfuscated Built-in Self Authentication -- 3D/2.5D IC based Obfuscation -- Part 5: Other Hardware Obfuscation Building Blocks -- Obfuscation and Encryption for Securing Semiconductor Supply Chain.
Keywords: Electronic circuits; Microprocessors; Computer architecture; Electronics; Cryptography; Data encryption (Computer science).; Electronic Circuits and Systems; Processor Architectures; Electronics and Microelectronics, Instrumentation; Cryptology